Inhibition and working memory: differential markers of arithmetic and solving problems difficulties in Kindergarten - Jessica Mercader Ruiz; Aída Puig Lleixà; Rosa Mª Rodrigo Carrión; Laura Abellán Roselló; Rebeca Siegenthaler Hierro (INFAD, 2019)
The aim of this study was to determine if the executive functions of working memory (WM) and inhibition are constituted as differential markers of arithmetic and problem solving difficulties at schooling beginning. The sample consisted of 208 kindergarteners aged 5 to 6 years (mean age = 70.17 months; SD = 3.51; 47.6% girls and 52.4% boys). Different executive functioning neuropsychological tasks were administered to assess visual and auditory inhibition, and verbal and viso-spatial WM. Participants were categorized into 4 groups based on their performance in the arithmetic and problem solving subtests of TEDI-MATH (Grégoire, Noël, and Van Nieuwenhoven, 2005): initial arithmetic difficulties (AD, n = 17) ; initial problem solving difficulties (PSD, n = 13); initial difficulties in both domains (AD + PSD, n = 20) and average performance (AP, n= 158). Results revealed a worse functioning of AD + PSD group in all tasks of inhibition and verbal WM compared to the AP group. Analysis also showed greater impairment of the AD group in visual inhibition and the PSD group in verbal WM in comparison with children without math problems. The task of auditory inhibition is the only one able to discriminate between DC + DRP group and children with difficulties in a single domain. No differences were found in the viso-spatial WM tasks. The implications of these findings for research and psychoeducational practice are discussed.